Análisis de los niveles de penetración de los servicios de telecomunicaciones más destacados que se ofrecen en el Ecuador - León Santín, Diana (2009)
The importance of conducting a study of these services is based upon the measure of how necessary technological development is in Ecuador as a developing nation. This project analyzes and evaluates different telecommunications services provided to the national territory. Our research centers upon data supplied by the public agencies responsible for regulating and controlling these telecommunication services. In our project, we provide a detailed statistical analysis of each service to determine the level of penetration in our nation in comparison to rates in other Latin American countries. Then, we use such analysis to make future service rate projections. Finally, we identify the position of Ecuador in relation to other countries within the International Union of Telecommunications.